A KAP Study on dengue prevention and surveillance among healthcare professionals in Narowal, Pakistan - Shamim Akhtar; Samreen Saleem; Mohsin Khan, Samina (Journal of the Pakistan Medical Association, 2025)
Objective: To assess the knowledge and practices of healthcare professionals regarding dengue prevention and surveillance systems, and to identify the relevant gaps. Method: The descriptive, cross-sectional study was conducted from October 2022 to January 2023 at the District Health Authority Hospital in Narowal, Pakistan, and comprised a range of healthcare professionals. Data was collected using a pre-tested, semi-structured questionnaire. Data was analysed using SPSS 22. Results: Of the 400 subjects with mean age 34.68±7.170 years, 271(67.8%) were females, 301(75.2%) had experience >10 years, 79(19.8%) were doctors and 321(80.2%) were nurses, paramedics or lady health visitors. Overall, 271(67.8%) subjects identified fever as a symptom of dengue, 203(50.8%) said dengue mosquitoes breed in clean water, 381(95.2%) could identify dengue-transmitting mosquitoes, 269(67.2%) said dengue mosquitoes bite during the daytime, and 133(33.2%) correctly stated that aspirin should not be given to dengue patients. Further, 289(72.2%) subjects considered dengue a serious illness, and 371(92.8%) believed it could be prevented. Additionally, 179(44.8%) subjects participated in community campaigns. Conclusion: There were significant areas for improvement in the knowledge, attitudes and practices related to dengue prevention among the healthcare professionals. Key Words: Knowledge, Attitude, Practices, Dengue, Preventive health Strategies, Disease surveillance, Healthcare professionals.